ANALISIS DAN PERANCANGAN SISTEM INFORMASI INVENTORY PADA CV . GIAT MANDIRI - Joko Susilo, S.Kom., MM., M.Kom (Jurnal Informatika dan Bisnis, 2017)
CV. Giat Mandiri is a commanditaire vennootschap that sells foodstuffs and the system used today is still in the manual category. This study uses several theories as a basis for performing analysis and design of information systems sales and inventory. The result of this research is an application of sales information system and inventory of goods. This application aims to facilitate the process of recording CV transactions, make reports quickly and accurately, and provide information about inventory.Â Keywords: information systems, inventory